2002
DOI: 10.1046/j.1440-6047.2002.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supplementary high calcium milk with additional magnesium on parathyroid hormone and biochemical markers of bone turnover in postmenopausal women

Abstract: The aim of this study was to investigate the impact of magnesium-enriched, high-calcium milk on serum parathyroid hormone (PTH) and biochemical markers of bone turnover in postmenopausal women. We recruited 50 healthy postmenopausal women to take part in this randomised controlled study. Half of the women consumed two serves of high-calcium skim milk enriched with magnesium (milk group) and half consumed two serves apple drink per day (apple group), each for 4 weeks. The milk provided 1200 mg calcium and an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…The supplementation of magnesium (106 mg) and calcium (1200 mg) for 4 weeks in postmenopausal women did not change the serum parathyroid hormone level both in the study and the control group. However, the supplementation increased the serum CTX (C-terminal telopeptide) level—i.e., a bone resorption marker [ 102 ]. A conducted meta-analysis indicated that a high magnesium intake was not associated with a lower risk of hip fractures.…”
Section: Minerals and Bone Mineral Density In Ibdmentioning
confidence: 99%
“…The supplementation of magnesium (106 mg) and calcium (1200 mg) for 4 weeks in postmenopausal women did not change the serum parathyroid hormone level both in the study and the control group. However, the supplementation increased the serum CTX (C-terminal telopeptide) level—i.e., a bone resorption marker [ 102 ]. A conducted meta-analysis indicated that a high magnesium intake was not associated with a lower risk of hip fractures.…”
Section: Minerals and Bone Mineral Density In Ibdmentioning
confidence: 99%
“…In a study in teenaged girls, magnesium balance was negative with calcium intakes of 1800 mg/d; however, compared with positive magnesium balance results with 800 mg calcium/d, the differences in magnesium absorption, excretion, and balance were not significant in this small crossover trial ( n = 5) ( 102 ). In a randomized clinical trial conducted in New Zealand menopausal women, researchers observed that the consumption of milk high in calcium or supplementation (1200 mg calcium) with or without magnesium significantly increased magnesium urinary excretion during the 8 h of consumption ( 103 ). Another trial in Thai menopausal women found that supplementation with 750 mg calcium for 3 mo led to a 15% increase in urinary excretion of magnesium, but the increase was not significant ( 104 ).…”
Section: Calciummentioning
confidence: 99%
“… 44 Milk not only acts on bone in children. It has been recognized already in 1985, 45 and reconfirmed later, that it inhibits bone turnover and resorption markers in postmenopausal women 46 47 48 and elderly men, and increases IGF-1. 49 …”
Section: Milk: General Commentmentioning
confidence: 88%